Magnetohydrodynamic Free Convection Flow with Thermal Radiation and Chemical Reaction Effects in the Presence of Variable Suction - Usman Halima; Uwanta Ime Jimmy; Ahmad Sama’ila Kamba (MATEC Web of Conferences, 2016)
The aim of the present study is to investigate the effect of flow parameters on the free convection and mass transfer of an unsteady magnetohydrodynamic flow of an electrically conducting, viscous and incompressible fluid past an infinite vertical porous plate in the presence of variable suction. The thermal radiation and chemical reaction effects are assumed to exist within the channel. Non dimensional partial differential equations of governing equations of flow are solved numerically using Crank Nicolson finite difference method. The skin friction, heat and mass transfer rates as well as the effects of various parameters on velocity, temperature and concentration profiles are analyzed. The signifiant results from this study are that an increase in the values of radiation parameter and chemical reaction parameter causes a reduction in the velocity, temperature and concentration.